Perlindungan Hukum Atas Hak Kekayaan Intelektual Karya Seni Musik Gamelan Bali - Anak Agung Ayu Gayatri; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Indonesia has a variety of traditional arts, one of which is Balinese gamelan music, along with the development of times as well as technology and the internet, a Balinese gamelan music art is easy for the public to enjoy but is prone to copyright infringement. The Balinese gamelan is a traditional Balinese musical instrument that has a unique sound which is then developed and preserved by Balinese artists in anticipation of the occurrence of sengkera, and to obtain legal certainty for creators of Balinese gamelan music in their work. The purpose of this study is to determine the legal arrangements for the intellectual property rights of Balinese gamelan music and to know the legal protection of intellectual property rights of Balinese gamelan music. By using normative research methods. Intellectual Property Rights consist of copyrights regulated in Law No.28 of 2014 concerning Copyright which regulates protected works, traditional cultural expressions, and law enforcement efforts through civil suits, criminal charges, arbitration and legal remedies and criminal sanctions. It is better if the Copyright Law regulates traditional music works of art in more detail and is developed by examining legal violations that occur through technological sophistication both domestically and abroad.